Optimum rates of surface‐applied coal char decreased soil ammonia volatilization loss. Issue 2 (16th March 2020) - Panday, Dinesh; Mikha, Maysoon M.; Collins, Harold P.; Jin, Virginia L.; Kaiser, Michael; Cooper, Jennifer; Malakar, Arindam; Maharjan, Bijesh
Abstract: Fertilizer N losses from agricultural systems have economic and environmental implications. Soil amendment with high C materials, such as coal char, may mitigate N losses. Char, a coal combustion residue, obtained from a sugar factory in Scottsbluff, NE, contained 29% C by weight. A 30‐d laboratory study was conducted to evaluate the effects of char addition on N losses via nitrous oxide (N2 O) emission, ammonia (NH3 ) volatilization, and nitrate (NO3 –N) leaching from fertilized loam and sandy loam soils. Char was applied at five different rates (0, 6.7, 10.1, 13.4, and 26.8 Mg C ha −1 ; char measured in C equivalent) to soils fertilized with urea ammonium nitrate (UAN) at 200 kg N ha −1 . In addition, there were two negative‐UAN control treatments: no char (no UAN) and char at 26.8 Mg C ha −1 (no UAN). Treatment applied at 6.7 and 10.1 Mg C ha −1 in fertilized sandy loam reduced NH3 volatilization by 26–37% and at 6.7, 10.1, and 13.4 Mg C ha −1 in fertilized loam soils by 24% compared with no char application. Nitrous oxide emissions and NO3 –N leaching losses were greater in fertilized compared with unfertilized soil, but there was no effect of char amendment on these losses. Because NO3 –N leaching loss was greater in sandy loam than in loam, soil residual N was twofold higher in loam than in sandy loam. This study suggests that adding coal char at optimal rates may reduce agricultural reactive N to the atmosphere by decreasing NH3 volatilization from fertilized soils.